Epistemologia da Ciência da Informação: inserção da área de Administração nas grades curriculares dos cursos de Biblioteconomia e/ou Ciência da Informação do Estado de São Paulo - Bastos Junior, José Carlos (Universidade Federal de São Carlos, 2012)
Given the changes caused by the explosion Informational, especially those caused by the emergence of Information and Communication Technologies (ICT), there was a need to train professionals able to work in this context. Thus, courses in librarianship in particular have sought to update their curricula in order to supply the demands of the labor market. Based on this need, this paper's main objective is to verify the impact caused by the insertion of subjects in the area of Administration in courses of Librarianship and/ or Information Science in Brazil. As subsidy for the research will be analyzed and compared the curricula of schools of librarianship public universities of the State of São Paulo, and these UFSCar, USP Ribeirão Preto, São Paulo USP and UNESP Marilia. Among the specific objectives, it was the changes in the curriculum resulted in a decrease analysis offers traditional disciplines (instrumental) of Librarianship, we classified the required courses and electives bars analyzed in four categories, these being instrumental, humanistic, technological, management and cross-border and, finally, were also analyzed their body teachers with the purpose of subsidizing the study. The methodology is to document research, which will focus on the theoretical studies of epistemology of information science and history courses in librarianship in Brazil. Regarding the results from analysis and subsequent comparison of said curriculum, it was observed that the subjects are present administrative content of at least 10% of subjects offered. It may also be noted that the content of instrumental disciplines (technical) still have space in their curricula.
Epistemology of Information Science: insertion of the Administration area in the curricula of Librarianship and/or Information Science courses in the State of São Paulo
Keywords: Grades curriculares; Administração; Ciência da Informação; Biblioteconomia; Curricula; Administration; Information Science; Librarianship; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA